Comparison of ashing and pyrolysis treatment on cadmium/zinc hyperaccumulator plant: Effects on bioavailability and metal speciation in solid residues and risk assessment. (1st March 2021) - Zhang, Jin; Wu, Shuai; Xu, Jialin; Liang, Peng; Wang, Minyan; Naidu, Ravi; Liu, Yanju; Man, Yu Bon; Wong, Ming Hung; Wu, Shengchun
Abstract: Phytoremediation of metal(loid)s contaminated sites is widely used, while there is scarce of investigation on the metal-enriched biomass waste safely disposal which resulted in risks of causing secondary pollution to the soil and water bodies and even to human health. Thus, this study compared the effects of ashing and pyrolysis treatments on cadmium (Cd) and zinc (Zn) hyperaccumulation plant Sedum plumbizincicola . Chemical speciation, the Toxicity Characteristic Leaching Procedure (TCLP), and diethylenetriamine pentaacetic acid (DTPA) extraction were employed to characterize the bioavailability and leachability of Cd and Zn in the solid residues after pyrolysis and ashing. The risk assessment code ( RAC ) and potential ecological risk index ( RI ) were subsequently used to evaluate the risk of the solid residues to the environment. The results showed that both ashing and pyrolysis treatments could transform the bioavailable Cd and Zn in S. plumbizincicola into a more stable form, and the higher the temperature the greater the stablility. Pyrolysis converted a maximum of 80.0% of Cd and 70.3% of Zn in S. plumbizincicola to the oxidisable and residual fractions, compared with ashing which achieved only a ∼42% reduction. The pyrolysis process minimised the risk level of Cd and Zn to the environment based on the RAC and RI assessments. The results of the TCLP test, and DTPA extraction confirmed that the leaching rate and the bioavailable portion of Cd and Zn in the biochars produced by pyrolysis were invariably significantly ( p  < 0.05) lower than the solid residues produced by ashing, and reached the lowest at 650 °C. In other words, pyrolysis was better than ashing for thermal treatment of the metal-enriched hyperaccumulator plant, in view of minimising the bioavailability and leachability of Cd and Zn from the solid residues to the environment. This study provides fundamental data on the choice of treatments for the disposal of metal-enriched plant biomass. Graphical abstract: Image 1 Highlights: The disposal of metal-enriched hyperaccumulator plant S. plumbizincicola were studied. Ashing and pyrolysis both could convert the bioavailable Cd & Zn to the stable state. Bioavailability of Zn & Cd were invariably lower in biochar than in ashing solid. Pyrolysis minimised the risk level of Cd & Zn to the environment than ashing. Pyrolysis was better than ashing on disposal of metal-enriched hyperaccumulator plant.